2013
DOI: 10.1590/s2317-15372013000200010
|View full text |Cite
|
Sign up to set email alerts
|

Seed performance of different corn genotypes during storage

Abstract: Corn seed producers have shown significant concern about variations in the seed storage potential of different hybrids, which may not perform as desired. The objective of this research was to evaluate the effect of storage conditions on the physiological potential of seeds of different corn genotypes. Three experimental corn hybrids, each represented by three seed lots produced by Syngenta Seeds, were evaluated. Seeds were stored for fifteen months under three environments: cold and dry chamber (10 ºC and 30% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
0
9
0
3
Order By: Relevance
“…-protective antioxidant mechanisms related to the activity of several enzymes such as catalase (CAT), alcohol dehydrogenase (ADH), superoxide dismutase (SOD), a and b amylase, malate dehydrogenase (MDH) and others as reported by different authors among them McDonald (1999), Corbineau (2012) and Timóteo and Marcos-Filho (2013). Some of these enzymes (biochemical markers) accumulate and others have progressively reduced synthesis and activity throughout deterioration; -variations in specific protein profiles, especially those related to respiration, lipid peroxidation and removal of free radicals could provide efficient indicators to monitor biochemical processes associated with seed vigor; -flow cytometry has opened new possibilities for quantification of cellular events, content and integrity of DNA, critical aspects related to the normal germination process and expression of seed vigor; -the evaluation of chlorophyll fluorescence is promising to the indirect determination of physiological potential of individual seeds by measurement of chlorophyll content (Cicero et al, 2009;Dell'Aquila, 2009); lack of degradation of this compound during seed maturation usually results negative effects on vigor.…”
Section: Perspectivementioning
confidence: 99%
“…-protective antioxidant mechanisms related to the activity of several enzymes such as catalase (CAT), alcohol dehydrogenase (ADH), superoxide dismutase (SOD), a and b amylase, malate dehydrogenase (MDH) and others as reported by different authors among them McDonald (1999), Corbineau (2012) and Timóteo and Marcos-Filho (2013). Some of these enzymes (biochemical markers) accumulate and others have progressively reduced synthesis and activity throughout deterioration; -variations in specific protein profiles, especially those related to respiration, lipid peroxidation and removal of free radicals could provide efficient indicators to monitor biochemical processes associated with seed vigor; -flow cytometry has opened new possibilities for quantification of cellular events, content and integrity of DNA, critical aspects related to the normal germination process and expression of seed vigor; -the evaluation of chlorophyll fluorescence is promising to the indirect determination of physiological potential of individual seeds by measurement of chlorophyll content (Cicero et al, 2009;Dell'Aquila, 2009); lack of degradation of this compound during seed maturation usually results negative effects on vigor.…”
Section: Perspectivementioning
confidence: 99%
“…Thus, it can be stated that the higher expression of CAT enzyme is related to the higher incidence of rot grains because of the deterioration of grains. According to Timoteo and Marcos -Filho (2013), while evaluating the seed storage in different environments, a higher CAT activity was observed in the controlled environment when compared to the laboratory and cold chamber. This increase might have occurred due to the environmental conditions, 20°C and 70% of relative humidity, which contributed to the acceleration of seed deterioration.…”
Section: Resultsmentioning
confidence: 99%
“…Vieira et al (2008) found that many seed dormancy types arise from the blockade of α-amylase action. Timóteo and Marcos-Filho (2013) propose that seed storage potential should be evaluated by germination and vigor assays, as well as through assessment of isoenzyme activity, including α-amylase. Wattanakulpakin et al (2012) showed that artiicially aged seeds have reduced α-amylase activity.…”
Section: A Lopes Et Almentioning
confidence: 99%